Effect of Oil Price Volatility on Clean Energy Stock Market Performance - Fazlollahi, Negar; Ebrahimijam, Saeed (Springer Science and Business Media B.V., 2017)
Recently clean energy firms become more attractive for the investors, this leads to the more comprehensive studies in this field. Thus the aim of this study is investigating the impact of oil price volatility on the performance of S&P500 clean energy market by contributing oil price and technology market performance. To explore this relation the Zivot-Andrews test was conducted to check the stationarity of the time series, since a structural break is found during year 2007–2008, and then Bound test co-integration is applied, because of different levels of integration among time series in order to check the probable existence of the long-run relationship in the model. The results indicate that clean energy sector performance converges to its long-run level by 1.09% speed of weekly adjustment. The most magnitude finding of this paper is that, oil price volatility has significant long-run effect on the performance of clean energy sector. However, no significant short-run impact is observable. © 2017, Springer International Publishing AG.
2nd International Conference on Banking and Finance Perspectives, ICBFP 2017 -- 2017-04-21 through 2017-04-21 -- Famagusta -- 272859
Keywords: Bound test; Clean energy stock price; Oil price; Oil price volatility; Technology stock price